2018
DOI: 10.22270/jddt.v8i6.2003
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro antimicrobial and antioxidant activity of Argyreia cuneata (Willd.) Ker Gawl. (Convolvulaceae)

Abstract: Objectives: Argyreia cuneata (Willd.) Ker Gawl. belongs to the family Convolvulaceae. The present study was performed to screen the potential of crude extract of various parts of A. cuneata to exhibit antimicrobial activity. Methods: Extraction of shade dried and powdered leaf, stem and flower of A. cuneata was carried out by maceration technique. Antibacterial and antifungal activity of extracts was evaluated by Agar well diffusion and Poisoned food technique respectively. Antioxidant activity was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The methanol extract have shown to scavenge ABTS with an IC 50 value of 13.91 μg/ml, while the ethyl acetate and chloroform extracts showed IC 50 of 16.52 μg/ml and 18.60 μg/ml, respectively. Similarly, Kekuda et al [25] , showed the maximum ABTS scavenging activity in methanol extract of Argyreia cuneata (willd.) Ker Gawl plant.…”
Section: Resultsmentioning
confidence: 81%
“…The methanol extract have shown to scavenge ABTS with an IC 50 value of 13.91 μg/ml, while the ethyl acetate and chloroform extracts showed IC 50 of 16.52 μg/ml and 18.60 μg/ml, respectively. Similarly, Kekuda et al [25] , showed the maximum ABTS scavenging activity in methanol extract of Argyreia cuneata (willd.) Ker Gawl plant.…”
Section: Resultsmentioning
confidence: 81%